Mutation Breeding, Genetic Diversity and Crop Adaptation to Climate Change. - Sivasankar, Sobhana. (CAB International, 2021)
International authors review achievements, new developments, trends and challenges in the field of plant mutation breeding, across the scientific community and the private sector. Chapters highlight specific challenges, such as emerging transboundary threats to crop production, and assess the overall importance of mutation breeding to food security.